Buckling Analysis of Three Circular Tubes - Syahirah Najmudin, Nor; Sahol Hamid, Yazmin; Parke, Gerry; Mansor, Hazrina (International Journal of Engineering and Technology, 2019)
Progressive collapse is a phenomenon in which a structure collapse continuously initiated by a local damage due to loss of one or a few load-carrying elements or disproportionately relative large region of it. Due to the fact that space truss structures are highly statically indeterminate structural system, where the failure of just only one critical member can result in the collapse of the entire structure, it is important to understand the buckling induced collapse mechanism before carrying out the design of the structure. This paper presents a study of three circular tubes as one the possible methods to improve the ductility and enhance the buckling capacity of steel tube truss members. This present study will involve numerical analysis using finite element software ABAQUS and results from the experiment data is compared. A full-scale assembly of a single truss steel member with application of three circular tubes is proposed and analyzed using finite element method for application in the critical members in the space truss system. In this paper improvement of local buckling resistance in the three circular tubes was stipulated which also highlights modelling techniques used for validation.Â Â